PERBEDAAN PERAN GENDER DALAM PERSEPSI PEMUKA AGAMA - Mami Hajaroh (LPPM UNY, 2002)
Abstract This is a survey research to reveal the perception of Islamic scholars toward the difference of gender role in Bantul Regency Yogyakarta Special Distric (DIY). The research sample is taken by using cluster samping. The area of Bantul Regency is divided into two classes i.e. the area border is determined proportionally. The data was collected using questionnaires and was analyzed with the aids of descriptive statistics cross break table. The research finding proved the tendency of the most Islamic Scholar to percept that the gender role difference in Islam does not subordinate women. It is shown by their perception about women position, the doctrine of testimony, inheritance, as well as trusteeship. Yet, there is still tending to percept women to be easier to be means to lead to ward the wrong path. The higher one’s educational level the smaller tendency to percept women in to subordinate position. Keywords: gender, perception